MODELLING THE FOOD SECURITY IN UKRAINE - Stavytskyy, A.V.; Prokopenko, O.O. (Ekonomika, 2014)
In the present paper, regional food security in Ukraine is investigated. Food security level is estimated using the developed integral indicator based on food availability and accessibility. The relationship between this indicator and some macroeconomic parameters is estimated with the help of the panel regression methods that allow to evaluate some specific features for each region and to summarize some general development trends.